2021
DOI: 10.1016/j.annonc.2021.08.400
|View full text |Cite
|
Sign up to set email alerts
|

119O Event-free survival (EFS), overall survival (OS), and safety of adding veliparib (V) plus carboplatin (Cb) or carboplatin alone to neoadjuvant chemotherapy in triple-negative breast cancer (TNBC) after ≥4 years of follow-up: BrighTNess, a randomized phase III trial

Abstract: Background: In BrighTNess, adding Cb with or without V to neoadjuvant chemotherapy significantly improved pathological complete response (pCR) with an acceptable safety profile in operable TNBC. We report EFS, OS, and second malignancies !4 years postsurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 0 publications
0
29
0
3
Order By: Relevance
“…Loibl et al presented their updates from the BrighTNess trial, a randomized phase III clinical trial, with three treatment arms and a total of 634 patients with TNBC: the established neoadjuvant regimen consisting of Paclitaxel alone (P) ( n = 158), Paclitaxel and Carboplatin alone (PCb) ( n = 160), and Paclitaxel, Carboplatin and the PPAR inhibitor Veliparib (PCbV) ( n = 316). Event-free survival, OS, and safety outcomes were assessed with a ≥4 years of follow-up period [ 28 ]. pCR was significantly improved when Carboplatin was added, with or without the addition of Veliparib, to Paclitaxel-based neoadjuvant chemotherapy.…”
Section: Chemotherapy For Triple Negative Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Loibl et al presented their updates from the BrighTNess trial, a randomized phase III clinical trial, with three treatment arms and a total of 634 patients with TNBC: the established neoadjuvant regimen consisting of Paclitaxel alone (P) ( n = 158), Paclitaxel and Carboplatin alone (PCb) ( n = 160), and Paclitaxel, Carboplatin and the PPAR inhibitor Veliparib (PCbV) ( n = 316). Event-free survival, OS, and safety outcomes were assessed with a ≥4 years of follow-up period [ 28 ]. pCR was significantly improved when Carboplatin was added, with or without the addition of Veliparib, to Paclitaxel-based neoadjuvant chemotherapy.…”
Section: Chemotherapy For Triple Negative Breast Cancermentioning
confidence: 99%
“…pCR was significantly improved when Carboplatin was added, with or without the addition of Veliparib, to Paclitaxel-based neoadjuvant chemotherapy. Also, adding Carboplatin to Paclitaxel improved pCR and EFS without increasing myelodysplastic syndrome or acute myeloid leukemia [ 28 ]. When compared to P alone, HR for EFS with PCbV was 0.63 (95% CI: 0.43–0.92, p = 0.016), and HR for EFS with PCb was 0.57 (95% CI 0.36–0.91, p = 0.018) [ 28 ].…”
Section: Chemotherapy For Triple Negative Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, pCR tended to be worse in the cisplatin- containing group than in the doxorubicin–cyclophosphamide group for BRCA carriers with early HER2-negative BC ( Tung et al, 2020b ). The BrightTNess trial demonstrated that the addition of carboplatin increased pCR ( Loibl et al, 2018a ) and improved event-free survival ( Loibl, 2021 ) compared with paclitaxel alone in unselected TNBC patients. Therefore, for germline BRCA mutation carriers with BC treated with neoadjuvant therapy, the routine addition of platinum to anthracycline and taxane-based chemotherapy is not supported.…”
Section: Treatment Of Breast Cancer With Brca1 Mut...mentioning
confidence: 99%
“…Pharmaceuticals 2021, 14, 1270 2 of 24 TNBC patients do not benefit from antihormonal or anti-HER2 therapy and receive conventional chemotherapy including doxorubicin (adriamycin), cyclophosphamide, and paclitaxel [15,16] (Figure 1). Platinum agents such as carboplatin are of increasing interest in gBRCA MUT , and more recently in BRCA-wild type (BRCA WT ) patients [15,17]. Paradoxically, TNBC patients tend to have a higher pathologic complete response (pCR) rate in the neoadjuvant setting (35-50%) versus other breast cancer subtypes, but still have poorer outcomes [18,19].…”
Section: Introductionmentioning
confidence: 99%